Caracterização morfofisiológica de populações de conilon provenientes de progenitores contrastantes para tolerância à seca - Silva, Francisco Davi da (2018)
The objective of this study was to study two populations from crosses of Coffea canephora var. Conilon (76-tolerant x 4-susceptible and 76x48-foldable) in relation to drought tolerance, by examining variations in a set of morphological, photosynthetic and compound concentrations in leaf tissues when subjected to drought in order to identify superior genotypes and select the most discriminatory variables for drought tolerance. The experiment was conducted without irrigation, at the Incaper Experimental Farm, in Marilândia - ES. The evaluations occurred in July / 2015, December / 2015 and April / 2016, the latter being the most critical drought period. Clone 76 showed superiority among the progenitor clones, and the population (pop.) 76x04 had better morphophysiological characteristics, compared to pop. 76x48, with a higher concentration of chlorophylls, carotenoids, less reduction in total leaf area, photosynthesis (A), stomatal conductance (gs), and transport rate of electrons (ETS). It also showed lower efficiency of water use (A/gs), which indicates greater effective water use. There was great variability between and within populations. The grouping analysis was performed using the unweighted pair group method with arithmetic mean (UPGMA), where 14 groups were found in July / 2015 and April / 2016 and 16 groups in December / 2015 for pop. 76x48, and seven groups in July and December / 2015, and six groups in April 2016 for pop. 76x04. By comparing the means of the groups obtained, we identified groups 9 and 10 of pop. 76x48, and groups 2 and 5 of pop. 76x04 as superior for drought tolerance. The specific leaf area (AFE), trait length (EC), ETR, A, gs and A / gs were the most important variables to discriminate individuals / groups regarding performance under water stress conditions.